Polarimetric Signatures of Sea Ice part II: Experimental Observations - Nghiem, S.V.; Kwok, R.; Yueh, S.H.; Drinkwater, M.R. (2004)
Experimental observations of sea ice polarimetric signatures in the Beaufort Sea under cold winter conditions are presented and interpreted with the composite model developed in Part I.